Extracellular vesicles: Potential role in osteoarthritis regenerative medicine - Wu, Xiaoxin (J Orthop Translat, 2019)
Osteoarthritis (OA) is a prevalent whole joint disease characterised by cartilage degradation, subchondral bone sclerosis and bone remodelling, and synovium inflammation, leading to pain, deformity, and cartilage dysfunction. Currently, there is no appropriate therapy for OA, and available treatments simply aim to reduce pain and swelling. Exosomes are membrane-bound extracellular vesicles secreted by almost all cells, receiving increasing interest because of their effect in cell-to-cell communication. Increasing evidence suggests that exosomes play an important role in cartilage physiological and pathological effects. This article reviews the potential role of exosomes in OA regenerative medicine. Special attention is given to mesenchymal stem cells-derived exosomes due to the extensive research on their cartilage repair property and their function as miRNA cargo. More investigations are needed for the effects of exosomes from synovial fluid and chondrocytes in joints. A better understanding of the mechanisms will contribute to a novel and promising therapy for OA patients. THE TRANSLATIONAL POTENTIAL OF THIS ARTICLE: A better understanding of the role of extracellular vesicles in regenerative medicine will contribute to a novel and promising therapy for OA patients.